Nexus between poverty gap and macroeconomic performance in the MENA region during the period 1990-2021 - Hassan, Fatma Ahmed (Technium Social Sciences Journal, 2023)
The study aims to explore the impact of some macroeconomic performance indicators on the poverty gap in the countries of the Middle East and North Africa (MENA) during the period 1990- 2021. The study used the econometric approach, where a correlation matrix was built between the variables, considering the poverty gap as a dependent variable, and four independent variables which are: the rate of inflation, the rate of population growth, the rate of economic growth, and the ratio of reserves to external debt. Applying the Unit Root test, and then the ARDL model to investigate the effect of independent variables on the poverty gap using E- Views 12. The study found that the results, in general, match with the economic theory, as in the short and long run, the rate of inflation increases the poverty rates in the (MENA) countries during the period 1990-2021; the decreasing ratio of reserves to external debt increase the poverty rates. The research also found that increasing exports had a positive impact on decreasing poverty in MENA region, while the population growth rate is associated with the most significant negative impact on poverty in those countries. The study confirmed that the effect of GDP growth on the poverty gap will be significant only after two lag periods. So, the study recommends applying economic policies that reduce inflation rates by using fiscal policy tools through reducing government spending or raising tax rates taking into account the need to support the poorest segments, raising export rates through an industrial and agriculture policy that supports the quality and competition of local products in global markets. We also recommend raising the reserve ratio to the total external debt, which may occur in the event of an improvement in export rates. It also requires population policies that reduce population growth rates. And finally, economic growth couldn’t reduce poverty without economic policies solving equality issues between different segments of the population.